Assessing the suitability of some Binh Dinh traditional martial art exercises for the health of the elderly - Nguyễn Ngọc Sơn; Bùi Trọng Duy; Trương Hồng Long (My University, 2019)
Assessing the suitability of some Binh Dinh traditional martial art exercises for the health of the elderly
Keywords: Võ cổ truyền Bình Định; Người cao tuổi; Độ phù hợp